Equalization and Standardization of Management of Education in Madrasah - Sumarto Sumarto (Hunafa: Jurnal Studia Islamika, 2017)
There are different views regarding the management of education. There are those who review management in terms of functions, objects, and institutions, and others who review management as a whole. Management is a series of activities that comprises planning, organizing, mobilization and supervision in achieving predetermined objectives, and aims to explore and utilize natural resources to achieve organizational goals. Based on this, management of education is interpreted as a series or activities such as planning, organizing, motivating, controlling, and developing all efforts to regulate and utilize human resources, facilities and infrastructure to achieve goals of education. To realize good management of education requires capable and talented leaders. In this paper, study is focused on equalization and standardization of management of education in Madrasah.